Logic with trees : an introduction to symbolic logic - Howson, Colin (Routledge, 1997)
Logic with Trees is a new and original introduction to modern formal logic. Preferring explanation and argument to intimidatingly rigorous development, Colin Howson presents the formal material in a clear and informal style that both beginners and those with some knowledge of formal methods will appreciate. Examples and exercises guide readers through the book, and answers to selected exercises at the end allow them to monitor their own progress.